Haptic media and the cultural techniques of touch: The sphygmograph, photoplethysmography and the Apple Watch. (October 2017) - O'Neill, Christopher
This article draws upon cultural techniques theory to propose an approach to studying haptic media as media technologies which train or discipline touch and which serve to produce touch itself as a coherent and 'proper' communicative technology. This article analyses the different forms of touch which have coalesced around the sphygmograph, a nineteenth-century pulse writing technology, and photoplethysmography, a contemporary heart rate–measuring technology which has been remediated as part of the Apple Watch. This article demonstrates that nineteenth-century clinicians drew upon the sphygmograph to authorise doctorly touch as newly 'proper' within a changed technological context. By contrast, an analysis of the place of error within the Apple Watch's photoplethysmograph demonstrates how contemporary self-quantifiers are encumbered with an unreliable measuring apparatus which can only generalise a form of 'improper' touch, touch which fails to know the body and which remains tied to a 'proper' touch which lies elsewhere.